2017
DOI: 10.4172/2168-9296.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Silencing miR-16 Expression Promotes Angiotensin II Stimulated Vascular Smooth Muscle Cell Growth

Abstract: miRNAs are a class of non-coding endogenous small RNAs that control gene expression at the posttranscriptional level and involved in cell proliferation, migration and differentiation. Dysregulation of miRNA expression is involved in a variety of human diseases including cardiovascular diseases. miRNAs have been shown to regulate vascular smooth muscle cell (VSMC) function and play vital roles in hypertension, restenosis and atherosclerosis. Here we reported that miR-16 as one of miRNAs in the miR-15 family was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Knockdown of endogenous miRNA-15b/16 in VSMCs attenuated VSMC-specific gene expression and promoted VSMC proliferation and migration [27]. A different mechanism of proliferation suppression was demonstrated for miRNA-16, which was observed to be highly expressed in VSMCs and to be involved in the Ang-II-mediated VSMC signaling pathways [28]. Lentiviral vector-mediated miRNA-16 knockdown promoted Ang-II-induced cell proliferation and migration, which was associated with the pathways involving ERK1/2 and p38MAPK [28].…”
Section: Mirnas Which Inhibit Vsmc Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of endogenous miRNA-15b/16 in VSMCs attenuated VSMC-specific gene expression and promoted VSMC proliferation and migration [27]. A different mechanism of proliferation suppression was demonstrated for miRNA-16, which was observed to be highly expressed in VSMCs and to be involved in the Ang-II-mediated VSMC signaling pathways [28]. Lentiviral vector-mediated miRNA-16 knockdown promoted Ang-II-induced cell proliferation and migration, which was associated with the pathways involving ERK1/2 and p38MAPK [28].…”
Section: Mirnas Which Inhibit Vsmc Proliferationmentioning
confidence: 99%
“…A different mechanism of proliferation suppression was demonstrated for miRNA-16, which was observed to be highly expressed in VSMCs and to be involved in the Ang-II-mediated VSMC signaling pathways [28]. Lentiviral vector-mediated miRNA-16 knockdown promoted Ang-II-induced cell proliferation and migration, which was associated with the pathways involving ERK1/2 and p38MAPK [28]. It was reported that the expression of miRNA-126 inhibited VSMC proliferation by targeting the low-density lipoprotein receptor-related protein 6 (LRP6) that is involved in a canonical Wnt pathway.…”
Section: Mirnas Which Inhibit Vsmc Proliferationmentioning
confidence: 99%
“…The direct target of miR-16 was programmed cell death 4 (PDCD4) [12]. Furthermore, the study of Gu et al [13] also reported lentiviral vector-mediated knockdown of miR-16 promoted Ang II-induced proliferation and migration in vascular smooth muscle cells. Microarray analysis and real-time PCR verified that miR-16 was significantly lower in the CAD patients than that in the non-CAD group [14].…”
Section: Introductionmentioning
confidence: 98%
“…For instance, miR‐16 represses SALL4 to inhibit the proliferation and migration of gastric cancer cells [ 10 ] ; its silencing promotes the proliferation of vascular smooth muscle cells treated with angiotensin II. [ 11 ] Nevertheless, it is unclear whether miR‐16 plays a role in PAH.…”
Section: Introductionmentioning
confidence: 99%